The EU–Ukraine Dispute Settlement Mechanisms (Discourse of Law and Administration, 2021)
The article analyses the essence of dispute settlement mechanisms existing in the framework of the EU–Ukraine relationship. It considers the evolution of the dispute settlement mechanisms over the last 30 years, types of mechanisms provided by the EU–Ukraine Association Agreement being in force. Particular attention is paid to the analysis of the first case of a trade dispute which is resolved using the arbitration procedure under the Association Agreement with Ukraine on the export of raw wood.
Keywords: Ukraine; the European Union; Association Agreement; dispute settlement; arbitration; mediation; essential close; trade dispute; timber